The Influence of Digital Financial Literacy and Digital Payment With Trust As A Moderating Variable on Sidoarjo Students' Purchase Intention in The Marketplace - Sarita, Jena (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study is aimed to investigate the effect of Digital Financial Literacy and Digital Payment with trust as a moderating variable on purchase intention of Sidoarjo’s Student in the Marketplace. This research use survey and quantitive approach. The population of this research is students of Digital Business 2021-2023. Purposive random sampling was used as sampling method in this research. By using Sugiyono (2020), the obtained minimum sample size was 30 respondents. The datas were collected by sharing the online questionnaires to the respondents. Data analysis was carried out using the Partial Least Square (PLS) method using Smart PLS version 4. The results of this research indicated: (1) Digital Financial Literacy affects significantly and positively toward consumer’s purchase intention (2) Digital payment has affect on consumer’s purchase decision (3) trust can moderate customer reviews on consumer’s purchase intentions.